MODERN APPROACHES OF TEACHING ENGLISH MYTHOLOGY TO STUDENTS (Scientific journal of the Fergana State University, 2026)
This article highlights the role of English mythology in the teaching of literature, culture, and language, and analyzes the theoretical and practical aspects of teaching it to university students through modern didactic approaches. The study explores the possibilities of developing students’ language competence, intercultural perception, and literary thinking based on mythological sources such as Beowulf, the legends of King Arthur, and Celtic folklore. The effectiveness of methods such as contextual reading, dramatization, visual techniques, comparative analysis, and creative expression in teaching mythology is substantiated. The topic is particularly relevant in the context of increasing interest in foreign language learning among Uzbek students.